Validation and adaptation of the Malay version of the Maslach Burnout Inventory. (April 2019) - Shoesmith, WD; Jalani, KJ; Abdullah, AC; Loo, JL; Tan, BY; Nordin, N; Giridharan, B; Fyfe, S; Forman, D
Abstract: This study aimed to validate and improve the Malay version of the Maslach Burnout Inventory. This is a widely used measure of staff burnout, which has previously been translated into Malay. Methods: The Malay version of the Maslach Burnout Inventory - Human Services Survey was pilot tested, altered, backtranslated and pilot tested again. The questionnaire was tested with all clinical staff in a psychiatric hospital in 2015. After analysis, the questionnaire was altered and tested again in 2016. Results: Four items (items 5, 11, 18, 20) were altered from the original after pilot testing, since it was clear that respondents were misinterpreting them. The questionnaire was returned by 154 out of 301 staff in July 2015 and by 121 out of 309 staff in July 2016, with 58 staff returning questionnaires in both years. Analysis of the data from the first year showed a Cronbach Alpha of less than 0.7 for the Emotional Exhaustion and Depersonalisation scales. Four items were dropped from the emotional exhaustion scale, due to non-loading onto the scale on PCA and low item-total correlation. Two items from the depersonalisation scale were retranslated. In the second year, the Cronbach's Alpha was now good for the emotional exhaustion scale (0.84), acceptable for the depersonalization scales (0.70) and acceptable for the personal accomplishment scale (0.79). Burnout negatively correlated with the Work Related Basic Satisfaction of Needs Scale, but did not correlate with the scales designed to measure collaboration. Conclusion: The original version of the scale was not reliable for all three subscales. The modified version of the scale was reliable and had both discriminant and convergent validity.